Serial Verb Constructions in Naija - (:unkn) unknown (My University, 2021)
This paper addresses the problems of documenting emerging languages through corpus syntactic annotation when dealing with large corpora with a strong probability of dialectal and social variation. To illustrate these problems, we have selected Serial Verb Constructions and the problems involved in their annotation and syntactic analysis in Naija, as done in the NaijaSynCor survey. In a bottom-up study of language, the concepts used for the annotation of a corpus are by large a pre-theoretical cover term, naturally problematic for typological and formal syntax. Such concepts are used in a dialectic process: (1) the prototypical typological concept and its defining properties are applied when annotating the corpus; (2) specificities of the language will emerge which fall outside the scope of the defining properties but do not prevent the concept to be used in the annotation; (3) a new set of properties emerges giving a new definition of the concept for the annotated language; (4) the prototypical properties present in what is identified as an SVC by the annotators help evaluate the distance between the language and the prototype.
Keywords: African Research